Viruses, screens and children: intertwining in times of pandemic (Simbiótica. Revista Eletrônica, 2020)
This paper discusses the uses of technology by children, who, through mobile phone cameras, tablets and computers, share their views on the COVID-19 pandemic in social networks. Through videos produced by boys and girls selected from Youtube and Instagran platforms, we will focus on the complex ways in which children and technology interact to produce forms and content of communication about the pandemic. We will show how their positions contribute to broadening the understanding of the challenges that now arise.Keyword: COVID-19; children; technology; sociology of childhood; sociology of technology.